2006
DOI: 10.1016/j.gca.2005.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Paleozoic ages and excess 40Ar in garnets from the Bixiling eclogite in Dabieshan, China: New insights from 40Ar/39Ar dating by stepwise crushing

Abstract: The 40 Ar/ 39 Ar stepwise crushing technique is applied for the first time to date garnet from ultra-high-pressure metamorphic (UHPM) eclogites. Three garnet samples from the Bixiling eclogites analyzed by 40 Ar/ 39 Ar stepwise crushing yield regular, predictable age spectra, and a clear separation between excess 40 Ar and concordant plateau and isochron ages. All three age spectra begin with high apparent ages followed by step by step decreasing ages, and finally age plateaux with apparent ages in the range f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 67 publications
(76 reference statements)
2
95
1
Order By: Relevance
“…From the Qinling segment, Jian et al (2000) presented Early Paleozoic zircon U-Pb ages for eclogites and interpreted them as the time of eclogite recrystallization, but later studies have interpreted these ages as reflecting magmatic crystallization rather than metamorphism Liu et al 2004bLiu et al , 2006. In the Dabie belt, Qiu and Wijbrans (2006) obtained similar 39 Ar/ 40 Ar ages on inclusions in garnets from the Bixiling eclogites, but the result has been criticized by Kendrick (2007) and Zhao and Gao (2007) for the consideration of the existence of excess argon. In the Sulu belt, Yang et al (2005) reported a zircon U-Pb age of 445 ± 4 Ma for an eclogite from the Qinglongshan locality (Fig.…”
Section: Proterozoic Metasomatic Modificationmentioning
confidence: 99%
“…From the Qinling segment, Jian et al (2000) presented Early Paleozoic zircon U-Pb ages for eclogites and interpreted them as the time of eclogite recrystallization, but later studies have interpreted these ages as reflecting magmatic crystallization rather than metamorphism Liu et al 2004bLiu et al , 2006. In the Dabie belt, Qiu and Wijbrans (2006) obtained similar 39 Ar/ 40 Ar ages on inclusions in garnets from the Bixiling eclogites, but the result has been criticized by Kendrick (2007) and Zhao and Gao (2007) for the consideration of the existence of excess argon. In the Sulu belt, Yang et al (2005) reported a zircon U-Pb age of 445 ± 4 Ma for an eclogite from the Qinglongshan locality (Fig.…”
Section: Proterozoic Metasomatic Modificationmentioning
confidence: 99%
“…It is noteworthy that even by applying sufficient crushing on pure K-rich mica at 400°C and 100-200 MPa (Dunlap and Kronenberg, 2001), the level of argon lost is likely to be insignificant, similar to the limit of resolution of typical dating studies, although Kendrick and Phillips (2009), while working on scapolite found a more significant contribution of what they argued to be lattice hosted argon while crushing. Moreover, it has been well documented that chemical components such as K, Ca, Cl and 40 Ar E and their ratios in fluid inclusions (by crushing) can be remarkably different from those of the solid phase (by heating crushed powders), although in some cases they yield identical ages (Turner and Bannon, 1992;Turner and Wang, 1992;Qiu, 1996;Qiu et al, 2002;Kendrick et al, 2006a,b;Qiu and Wijbrans, 2006, 2008Qiu and Jiang, 2007;Kendrick and Phillips, 2009). …”
Section: Possible Argon Reservoirs Contributing To Degassingmentioning
confidence: 99%
“…And if sufficient potassium exists inside, the fluid inclusions can yield meaningful isochron ages by the 40 Ar-39 Ar crushing technique [11][12][13][14][15][16][17]. Abundant CO 2 -CH 4 -saline secondary inclusions occurred in this quartz from container volcanic rock, providing a good analysis object for the 40 Ar-39 Ar crushing technique to determine the CO 2 gas emplacement age.…”
Section: Principlementioning
confidence: 99%
“…A few kinds of minerals formed during oil/gas accumulations and most of them are carbonates, not suitable for traditional isotopic dating methods. As to reservoir authigenic minerals, such as authigenic illite and authigenic K-feldspar 40 Ar-39 Ar(K-Ar) ages constrain the maximum ages, but not the exact oil/gas emplacement ages. In addition, it is very difficult to separate high-purity authigenic illite with present mineral separation techniques [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation